Graph coloring techniques for planning dynamic optical networks - Fonseca, Pedro Afonso Fernandes (2021)
Dynamic optical networks will be crucial in global optical communications in the next 5-10 years.On-demand services, fuelled by applications such as cloud computing and grid computing, are the main drivers for the availability of an increasingly dynamic network infrastructure. Efficient network planning tools that deal with Routing and Wavelength Assignment problems are of paramount relevance in this dynamics cenario. In this work, a simulator for planning dynamic optical networks was developed, and several real networks were tested, such as National Science Foundation Network, British Telecom, US Backbone Network, and also bidirectional ring networks. In this simulator, we have implemented a graph coloring wavelength assignment algorithm named Small-Bucket algorithm that allows recoloring to occur. A comparison performance with the First-fit algorithm is performed in terms of the blocking probability, number of recolorings, number of colors used and simulation time. It is concluded that the Small-Bucket algorithm originate slower blocking probabilities than the ones obtained with the First-fit algorithm. However, to reach these low blocking probabilities, the Small-Bucket algorithm makes use of a larger number of wavelengths and recolorings.